Anticaries effect of toothpaste with nano-sized sodium hexametaphosphate - Garcia, Luhana Santos Gonzales [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Pessan, Juliano Pelim [UNESP]; dos Passos Silva, Matheus [UNESP]; Neto, Francisco Nunes Souza; Gorup, Luiz Fernando; de Camargo, Emerson Rodrigues; Danelon, Marcelle [UNESP] (Springer Nature, 2019)
Objective: To evaluate the effect of a fluoride toothpaste containing nano-sized sodium hexametaphosphate (HMPnano) on enamel demineralization on the biochemical composition and insoluble extracellular polysaccharide (EPS) in biofilm formed in situ. Methods: This crossover double-blind study consisted of four phases (7 days each), in which 12 volunteers wore intraoral appliances containing four enamel bovine blocks. The cariogenic challenge was performed using 30% sucrose solution (6×/day). Blocks were treated 3×/day with the following toothpastes: no F/HMP/HMPnano (Placebo), conventional fluoride toothpaste, 1100 ppm F (1100F), 1100F + 0.5% micrometric HMP (1100F/HMP), and 1100F + 0.5% nano-sized HMP (1100F/HMPnano). The percentage of surface hardness loss (%SH), integrated loss of subsurface hardness (ΔKHN), and enamel calcium (Ca), phosphorus (P), and fluoride (F) were determined. Moreover, biofilms formed on the blocks were analyzed for F, Ca, P, and insoluble extracellular polysaccharide (EPS) concentrations. Data were analyzed using one-way ANOVA, followed by Student–Newman–Keuls’ test (p < 0.001). Results: 1100F/HMPnano promoted the lowest %SH and ΔKHN among all groups (p < 0.001). The addition of HMPnano to 1100F significantly increased Ca concentrations (p < 0.001). The 1100F/HMPnano promoted lower values of EPS when compared with 1100F (~ 70%) (p < 0.001) and higher values of fluoride and calcium in the biofilms (p < 0.001). Conclusion: 1100F/HMPnano demonstrated a greater protective effect against enamel demineralization and on the composition of biofilm in situ when compared to 1100F toothpaste. Clinical relevance: This toothpaste could be a viable alternative to patients at high risk of caries.
Keywords: Biofilm; Caries; Demineralization; Fluoride; Nano-sized